1975
DOI: 10.1126/science.190.4213.461
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Atmospheric Particulate Matter from the Eruption of Heimaey, Iceland

Abstract: The chemical composition of atmospheric particulate matter and rock samples collected on the island of Heimaey after the January 1973 eruption indicates that volcanic activity is a possible source of global significance for particulate material containing elements such as Br, Se, Sb, and Zn. Atmospheric aerosols from such remote areas as the North Atlantic Ocean and the South Pole are found to be highly enriched in these elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Annual elemental fluxes (Table 6) can be calculated by extrapolation of the daily fluxes in Table 5 (Lepel et al, 1978); E = Mount Etna 1987 (this study); H = Heimaey 1973 (Mroz and Zoller, 1975); M = Mount Etna 1976 (Buat-M6nard and Arnold, 1978); P = Pu'u O'o 1983O'o -4 (Crowe et al, 1987 creased emission rates during activity periods more intense than those observed during this study. For example, the data of Bruno et al (1989) and Allard et al ( 1991) suggest that the long-term degassing rate of Mount Etna may be four times less than that observed during this study.…”
Section: Volcanic Versus Anthropogenic Fluxesmentioning
confidence: 99%
“…Annual elemental fluxes (Table 6) can be calculated by extrapolation of the daily fluxes in Table 5 (Lepel et al, 1978); E = Mount Etna 1987 (this study); H = Heimaey 1973 (Mroz and Zoller, 1975); M = Mount Etna 1976 (Buat-M6nard and Arnold, 1978); P = Pu'u O'o 1983O'o -4 (Crowe et al, 1987 creased emission rates during activity periods more intense than those observed during this study. For example, the data of Bruno et al (1989) and Allard et al ( 1991) suggest that the long-term degassing rate of Mount Etna may be four times less than that observed during this study.…”
Section: Volcanic Versus Anthropogenic Fluxesmentioning
confidence: 99%
“…The bentonites themselves, however, contain less selenium than the surrounding sediments with one exception (SDGS-439.6). Several studies (Byers et al, 1936;Mroz and Zoller, 1975;Lepel et al, 1978) have demonstrated that during volcanic activity, atmospheric aerosols and fumarole deposits may be enriched in Se by a Table 4. Proportion of total Se mobilized by each step of the sequential extraction protocol, representing average values for "Treatment C" of each sequential step.…”
mentioning
confidence: 99%
“…Iron and manganese in the airborne dust in remote areas are generally considered to originate from the soil materials, whereas the origins of zinc and copper in the airborne dust in remote areas are considered to be the global fallout of volcanic ejecta from major eruptions (Mroz and Zoller, 1975;Hirose et al, 1982) and/or anthropogenic sources (Rahn, 1971). This viewpoint is supported by the fact that the enrichment of zinc and copper in the airborne dust in remote areas is one or two order higher than that of iron and manganese and that the pattern of the size distribution for the copper and zinc bearing particles in the air is generally different from that of the iron and manganese bearing particles.…”
Section: Resultsmentioning
confidence: 99%